Auricular acupoint pressing and nursing of a patient with pneumonia and diabetes mellitus (耳穴压丸治疗1例糖尿病合并肺炎患者的护理体会) - HAN Jinghua (韩精华) (中西医结合护理)
This paper summarized the auricular acupoint pressing therapy and nursing management for a patient with pneumonia and diabetes mellitus. Based on the routine nursing and health education, auricular acupoint pressing therapy was carried out to alleviate cough, reduce sputum production and control the blood sugar level. The auricular acupoint pressing therapy is an easy-to-use nursing technique with less adverse reactions and high patient acceptance (本文总结1例耳穴压丸治疗糖尿病合并肺炎的护理经验, 在常规干预的基础上实施耳穴压丸辅助治疗, 同时做好基础护理、健康教育等护理措施, 能有效缓解患者咳嗽咳痰症状, 进一步稳定血糖水平, 且该操作简单易行、不良反应少, 患者的接受度较高。)